Electromagnetic separation of silicon from metallurgical-grade silicon refined slag during the remelting process - Han, Shifeng; Tan, Ning; Wei, Kuixian; Ma, Wenhui (Separation and purification technology, 2022)
•The Si recovery from MGSRS is significant for MG-Si industry.•The Si from MGSRS cannot be completely separated via the direct remelting.•An idea of electromagnetic separation Si from MGSRS was proposed.•Electromagnetic separation is beneficial to the Si recovery from MGSRS.•This study shows broad application prospects for the Si recovery from MGSRS. The recovery of silicon from metallurgical-grade silicon refined slag (MGSRS) is of great significance for improving the utilization of silicon resources and increasing production profits. Currently, the main treatment method of MGSRS is crushing and manual selection. However, this method is characterized by the low recovery rate of silicon and lower production efficiency. In this study, a novel investigation was conducted to overcome these disadvantages and explore the separation behaviors of silicon from MGSRS. Moreover, direct remelting and electromagnetic induction remelting was conducted to determine why it is difficult to completely separate the slag and silicon in MGSRS, and to study the behaviors of silicon in different remelting methods. The results indicate that silicon is subject to the weak resultant force of gravity and buoyancy, which makes it difficult to move under the constraint of viscous force during direct remelting, and ultimately leads to the failure of separation from the MGSRS. On the contrary, under electromagnetic induction remelting conditions, silicon will aggregate to the center of the electromagnetic field to form bulk silicon, which can be separated from MGSRS. Ultimately, the results of this research confirm that electromagnetic induction remelting is a feasible alternative for the recovery of silicon from MGSRS. This study provides a new concept for the recovery of silicon from MGSRS, and is conducive to the development of related technologies in the future.